SARS-CoV-2 breakthrough infections during the second wave of COVID-19 at Pune, India - Doke, Prakash P.; Mhaske, Suhas T.; Oka, Gauri; Kulkarni, Ruta; Muley, Vrishali; Mishra, Akhilesh Chandra; Arankalle, Vidya A. (Frontiers in Public Health, 2023)
Breakthrough infections following SARS-CoV-2 vaccination remain the global concern. The current study was conducted during the second wave of COVID-19 (1st March- 7th July 2021) in Pune, India, at two tertiary care hospitals. Of the 6159 patients diagnosed as COVID-19, 372/2210 (16.8%) were breakthrough infections. Of these, 81.1% and 18.8% received one or two doses of Covishield or Covaxin respectively. Of note, 30.7% patients were with comorbidities, hypertension being the commonest (12.44%). The majority of infections were mild (81.2%). Forty-three patients with breakthrough infections were hospitalized with severe (n=27, 62.8%) or moderate (n=16, 37.2%) disease. The receptor binding domain (RBD) sequences from vaccinated (n=126) and non-vaccinated (n=168) samples were used for variant analysis. The delta variant was predominant followed by kappa in both vaccinated and non-vaccinated groups. Viral load (qRT-PCR) was not different among these categories. Full-genome comparisons of sequences in relation to vaccination status did not identify any mutation characteristic of the vaccinated group. Irrespective of the number of doses, neutralizing antibody titers (PRNT50) during the first week of clinical disease were higher in the vaccinated patients than the unvaccinated category. In conclusion, though not completely, SARS-CoV-2 vaccines used for country-wide immunization did reduce disease severity among the individuals without any comorbidity by inducing rapid immune response against distinctly different delta and kappa variants. The utility against emerging variants with further mutations need to be carefully examined.